2018
DOI: 10.3126/jnhrc.v16i2.20307
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Production and Antimicrobial Resistance among Uropathogens in Pediatric Cases: a Hospital Based Study

Abstract: Background: The study was designed to provide account of etiological agents of urinary tract infection in pediatric patients and the antimicrobial resistance pattern plus biofilm producing profile of the isolates.Methods: The prospective study was conducted in Alka Hospital, Nepal with 353 clean catch urine samples from children. It was obtained during July 2014 to January 2015 which were first cultured by semi-quantitative method, followed by antimicrobial susceptibility testing and biofilm production assay o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This has important implications considering that a significant percentage of carbapenem-resistant isolates in some areas are MBL-producers 11,[92][93][94] . In contrast, the combination aztreonam/avibactam can restore activity against MBL-producing isolates, 95, [97][98][99] Other less studied combinations may also be useful. Notable is the in vitro synergy of colistin with agents such as linezolid, vancomycin and teicoplanin in colistin-resistant GNB strains.…”
Section: Synergistic Combinations For Pdr Infectionsmentioning
confidence: 99%
“…This has important implications considering that a significant percentage of carbapenem-resistant isolates in some areas are MBL-producers 11,[92][93][94] . In contrast, the combination aztreonam/avibactam can restore activity against MBL-producing isolates, 95, [97][98][99] Other less studied combinations may also be useful. Notable is the in vitro synergy of colistin with agents such as linezolid, vancomycin and teicoplanin in colistin-resistant GNB strains.…”
Section: Synergistic Combinations For Pdr Infectionsmentioning
confidence: 99%
“…Klebsiella was usually found to be the second most frequent uropathogen unlike our study in which Proteus was more frequently isolated. [24][25][26] In our study, gram-negative rods demonstrated the highest resistance against ampicillin followed by Norfloxacin. Previous studies from Pakistan have also demonstrated high resistance against ampicillin.…”
Section: Discussionmentioning
confidence: 93%